1978
DOI: 10.1128/iai.21.3.973-977.1978
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasma capsulatum infection in nude mice

Abstract: Congenitally athymic nude (nu/nu) mice, when injected intraperitoneally with Histoplasma capsulatum, developed a rapidly fatal disseminated infection characterized by heavy parasitization of reticuloendothelial tissues. In contrast, their heterozygous (nu/X) littermates, which possessed a functioning thymus, developed only a low-grade infection which was apparently self-limited and rarely fatal. Transplantation of thymic tissue into nu/nu mice diminished greatly the severity of infection and reduced mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 17 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…The following experimental evidence indicates that the major component of protective immunity to histiplasmosis is mediated by T lymphocytes: (1) adoptive immunity in recipients conferred by immune T lymphocytes persisted for at least 12 weeks after cell transfer, (2) immune peritoneal cells were far more efficient than spleen cells in adoptive transfer of immunity, (3) removal of plastic-adhering cells from lymphoid cells prior to transfer did not alter their protective activity, (4) prior treatment with anti-theta serum or mitomycin C ablated the ability of immune lymphocytes to confer immunity, and (5) treatment with antiserum to IgG did not alter the protective activity of immune lymphocytes. These findings are also in accord with the observations of Williams et al (22), who showed that congenitally athymicnude (nu/nu) mice, when injected i.p. with yeast cells of H. capsulatum, developed rapidly fatal disseminated disease, whereas their heterozygous (nu/+) littermates, with functioning thymus, had a low grade, self-limited infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The following experimental evidence indicates that the major component of protective immunity to histiplasmosis is mediated by T lymphocytes: (1) adoptive immunity in recipients conferred by immune T lymphocytes persisted for at least 12 weeks after cell transfer, (2) immune peritoneal cells were far more efficient than spleen cells in adoptive transfer of immunity, (3) removal of plastic-adhering cells from lymphoid cells prior to transfer did not alter their protective activity, (4) prior treatment with anti-theta serum or mitomycin C ablated the ability of immune lymphocytes to confer immunity, and (5) treatment with antiserum to IgG did not alter the protective activity of immune lymphocytes. These findings are also in accord with the observations of Williams et al (22), who showed that congenitally athymicnude (nu/nu) mice, when injected i.p. with yeast cells of H. capsulatum, developed rapidly fatal disseminated disease, whereas their heterozygous (nu/+) littermates, with functioning thymus, had a low grade, self-limited infection.…”
Section: Discussionsupporting
confidence: 93%
“…It is generally accepted that the primary host defense mechanism activated in response to infection by Histoplasma capsulatum is the cell-mediated arm of the immune response. Evidence for this concept is provided by several experimental studies: first, lymphocytes from mice immunized by sublethal infection with H. capsulatum can mediate suppression of intracellular growth of the fungus in normal mouse macrophages (8); second, the increased susceptibility of congenitally athymic mice (22) or conventional mice after treatment with antilymphocyte serum and cytotoxicagents (1,4,6); and third, the adoptive transfer ofanti-Histoplasma immunity by spleen or peritoneal cells from immunized donors (15,16,21). We have previously shown that the immunity elicited by sublethal infection or by immunization of mice with ribosomal preparations from yeast cells of H. capsulatum is mediated by T-lymphocytes and that their active proliferation in recipients is necessary for expression ofthe protective immunity (16).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally held that a critical host defense mechanism activated in response to infection by Histoplasma capsulatum is the so-called cellmediated immune response. Support for this concept is provided by several experimental studies: first, by the demonstration that lymphocytes from mice immunized by sublethal infection with H. capsulatum can mediate suppression of intracellular growth of the fungus in normal mouse macrophages (17); second, by demonstration of increased susceptibility to Histoplasma infection in congenitally athymic mice (38) or in conventional mice after treatment with antilymphocyte serum and cytotoxic agents (1,8,12); and third, by evidence for transfer of adoptive immunity against Histoplasma by spleen or peritoneal cells from immunized donors (36).…”
mentioning
confidence: 99%
“…Cell-mediated immune responses are of primary importance in protective immunity to histoplasmosis and in diseases caused by other facultative intracellular parasites. In histoplasmosis the evidence for this concept is provided by several studies: first, lymphocytes from mice immunized by sublethal infection with Histoplasma capsulatum can mediate suppression of growth of the fungus within normal macrophages (7,8); second, the higher susceptibility of congenitally athymic mice (24) or normal mice following treatment with antilymphocyte serum and cytotoxic agents (1,6); and third, the adopive transfer of anti-Histoplasma immunity by spleen and peritoneal cells from immunized donors (9, 19,21,25).…”
Section: Introductionmentioning
confidence: 99%